True four quadrant matrix converter induction motor drive with servo performance - Sunter, Sedat; Clare, Jon C. (IEEE, 1996)
This paper describes the development of a 2.5 kW high performance vector controlled induction motor servo drive with true four quadrant capability employing a matrix converter power circuit. The advantages of this system over the conventional rectifier-inverter arrangement are: capability for regeneration into the utility, sinusoidal supply currents and minimum passive components. Solutions to the special problems associated with the power circuit and implementation of closed-loop control in the matrix converter drive are given. Comprehensive experimental results demonstrating the performance of the drive system are presented.
Proceedings of the 1996 27th Annual IEEE Power Electronics Specialists Conference, PESC. Part 1 (of 2) -- 1 January 1996 through 1 January 1996 -- Maggiore, Italy -- 45397
Keywords: Algorithms; Closed loop control systems; Electric currents; Electric network synthesis; Induction motors; Modulation; Power converters; Power supply circuits; Servomotors; Systems analysis; Induction motor drive; Matrix converter; Matrix converter drives; Electric drives